2003
DOI: 10.1016/s0736-0266(02)00107-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine on bone mass and strength in aged female rats

Abstract: This study investigated the effects of nicotine on bone mass and biomechanical properties in aged, estrogen-replete (shamoperated) and estrogen-deplete (ovariectomized) female rats. Eight month old, retired breeder, sham-operated and ovariectomized Sprague-Dawley rats were left untreated for 12 weeks to establish cancellous osteopenia in the ovariectomized group. The animals were then administered saline, low dose nicotine (6.0 mg/kg/day) or high dose nicotine (9.0 mg/kg/day) via osmotic minipumps for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Despite smoking being considered one of the main risk factors to osteoporosis, most of the animal studies yet conducted have not reported a correlation between nicotine (one of the main compounds of cigarette smoke) administration and lower bone density 2,9,24,25 . A previous study of ours also reported that nicotine * did not present a negative impact on bone healing around implants inserted in tibiae of rabbits 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite smoking being considered one of the main risk factors to osteoporosis, most of the animal studies yet conducted have not reported a correlation between nicotine (one of the main compounds of cigarette smoke) administration and lower bone density 2,9,24,25 . A previous study of ours also reported that nicotine * did not present a negative impact on bone healing around implants inserted in tibiae of rabbits 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study has already suggested that a higher incidence of poor bone quality is observed in smokers 4 . Although most of the animal studies conducted have not reported a correlation between nicotine administration and lower bone density 2,9,24,25 , nicotine is just one of the potentially toxic compounds of cigarette smoke. Still, the number of studies evaluating the effect of cigarette smoke as a whole and smoking cessation on bone is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the reason why BMD increases with regard to baseline in femoral midshaft in all groups within 12 weeks following ovariectomy and starts to decrease after 12 weeks (Jiang et al, 1998;Jiang et al, 1997) may be the use of young (18 week) rats which skeletal development is faster. In a study, it is reported that BMD and Lmax in femoral midshaft decrease after 12 weeks following OVX in 32 week rats (Akhter et al, 2003), while no significant change is determined in femoral midshaft of 12 week rats in another research (Zhang et al). These different results may have been caused by different levels of osteopenia due to difference in the age of the animals at OVX and different post-ovariectomy periods (Patlas et al, 2000).…”
Section: Discussionmentioning
confidence: 93%
“…The effects of nicotine alone on bone health are not conclusive (Table) [22,24,[29][30][31][32][33]. On the other hand, numerous clinical studies have consistently documented the deleterious impact of smoking on bone healing and spinal fusion [2,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%